The Influence of Product Quality, Service Quality, and Perception of Coal Prices on Customer Satisfaction at PT Bukit Asam, Tbk - Rahman, Beno; Widiyanti, Marlina; Saggaff Shihab, Muchsin; Rosa, Aslamia (Devotion : Journal of Research and Community Service, 2024)
This study was conducted with the aim of determining the influence of product quality, service quality and coal price perception on customer satisfaction at PT Bukit Asam, Tbk. The population in this study is all consumers or companies that purchase coal at PT Bukit Asam in the Tanjung Enim Mining Unit, Tarahan Port Unit and Kertapati Pier Unit in 2023 to 2024. The sample used in this study was 100 respondents using the purposive sampling method. The results of multiple linear regression analysis show that product quality, service quality and coal price perception have a positive and significant effect on customer satisfaction. Product quality, it is expected for PT Bukit Asam, Tbk to be able to provide innovation both in terms of offers, marketing and promotions carried out. The quality of service, PT Bukit Asam, Tbk is expected to be quick in responding and providing information. Price perception, it is hoped that PT Bukit Asam, Tbk can adjust in providing the price of coal offered.